Typification of the Linnaean names Oxalis flava and O. versicolor (Oxalidaceae) - Ferrer-Gallego, Pedro Pablo; Altinordu, Fahim (Phytotaxa, 2015)
The typification of the Linnaean names Oxalis flava and O. versicolor (Oxalidaceae) are discussed. The illustrations provided by Burman in Rariorum Africanarum Plantarum are designated as the lectotypes of these names. Furthermore, an epitype for the name O. versicolor is also designated in order to avoid any ambiguity in the interpretation of the lectotype.